Optimal design and development of a five-bar finger with redundant actuation - Lee, JH; Yi, BJ; Oh, SR; Suh, IH (PERGAMON-ELSEVIER SCIENCE LTD, 2001)
In order to develop a human hand mechanism, a five-bar finger with redundant actuation is designed and implemented. Each joint of the finger is driven by a compact actuator mechanism having an ultrasonic motor and a gear set with a potentiometer, and controlled by a VME bus-based control system. Optimal sets of actuator locations and link lengths for cases of a minimum actuator, one-, two-, and three-redundant actuators are obtained by employing a composite design index which simultaneously considers several performance indices, such as workspace, isotropic index, and force transmission ratio. According to the optimization result, several finger-configuration optimized for a special performance index are illustrated, and it is concluded that the case of one redundant actuator is the most effective in comparison to the cases of more redundant actuators, and that the case of two redundant actuators is the most effective in multi-fingered operation in which the force characteristic is relatively important, as compared to the kinematic isotropy and the workspace of the system. (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: MECHANISM; HAND